ARE YOU MAKING A MEAL OUT OF RESEARCH? - Reay, Stephen (Stephen David) ([S.l.])
1 online resource
Keywords: Those new to research often end up making a meal of it' because it can be tricky to know exactly where to begin. But it doesn't have to be so daunting. This workbook has been designed mostly for those going into postgraduate study, but it can also be used by anyone looking to start their journey into research. It will help you better understand what research is, how to do it (with activities to help you think about this in the context of your own research) and where you might start looking in the vast ocean of resources out there.